1978
DOI: 10.1002/aja.1001530309
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral localization of insulin by immunofluorescence

Abstract: An immunohistochemical procedure was used to detect cells which appear to bind insulin in the mouse brain. Strong fluorescence was observed in the cell bodies and processes of tanycytes lining the third ventricle and in the choroid plexi. These findings suggest that insulin enters the central nervous system, and indicate a route for its possible transport. This adds credence to earlier observations that the hypothalamic ependymal cells and processes form a highly organized and functional system, with different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Insulin has been detected in the brain (7,8,76,77), which was thought to be an insulin-independent organ because insulin cannot pass through the blood-brain barrier. The distribution of insulin receptors was investigated in the brain by in vitro radioautography (78)(79)(80)(81), and insulin receptor mRNA was demonstrated in rat brain by in situ hybridization (82).…”
Section: Histologic Distribution Of Insulin Receptorsmentioning
confidence: 99%
“…Insulin has been detected in the brain (7,8,76,77), which was thought to be an insulin-independent organ because insulin cannot pass through the blood-brain barrier. The distribution of insulin receptors was investigated in the brain by in vitro radioautography (78)(79)(80)(81), and insulin receptor mRNA was demonstrated in rat brain by in situ hybridization (82).…”
Section: Histologic Distribution Of Insulin Receptorsmentioning
confidence: 99%
“…Early studies that investigated the distribution of insulin receptor in the brain reported that, in addition to the BBB, choroid plexuses also possessed a high insulin binding capacity [91, 92]. Computerized densitometric analyses indicated that choroid plexus actually displayed the highest density of insulin binding sites among all brain structures [92, 93].…”
Section: Routes Of Drug Delivery Into the Csf Through The Choroid Plexusmentioning
confidence: 99%
“…Computerized densitometric analyses indicated that choroid plexus actually displayed the highest density of insulin binding sites among all brain structures [92, 93]. In situ hybridization confirmed the expression level of the insulin receptor gene in choroid plexus [94].…”
Section: Routes Of Drug Delivery Into the Csf Through The Choroid Plexusmentioning
confidence: 99%
“…The origin of insulin in the brain has been a matter of debate until relatively recently (Gray et al, 2014). Early observations documented the presence of insulin in the cerebrospinal fluid (CSF) and the brain (Margolis and Altszuler, 1967;Pansky and Hatfield, 1978). Because expression of insulin by brain cells was firmly established only recently (Kuwabara, 2011), for many years, insulin actions in the brain were assumed to arise from pancreatic insulin (Schwartz and Porte, 2005) that has to cross the blood-brain-barriers (BBBs).…”
Section: Introductionmentioning
confidence: 99%